Kepentingan Geopolitik Vietnam Bergabung dalam Keanggotaan Lancang-Mekong Cooperation Tahun 2018 - Lestari, Dian Trianita; Suaib, Eka; Lisna, Lisna (Jurnal Ilmiah Hubungan Internasional, 2023)
Vietnam opposes the policies that have been made by upstream countries regarding dam construction projects in the Mekong River region which have brought huge losses to upstream countries. Vietnam, aware of the importance of water sources on the Mekong River, has finally rejoined the Lancang-Mekong Cooperation (LMC). In this article, the author presents an analysis of Vietnam's geopolitical interests in joining LMC membership using the concept of Geopolitics. The method used is descriptive with data collection techniques through literature study and documentation. The research results show that Vietnam's geopolitical interest in joining LMC membership is influenced by two factors, namely domestic factors consisting of managing water resources and international factors consisting of China's economic power in regulating and suppressing countries through which the Mekong River flows. The LMC program focuses on 3+5, where 3 refers to the three pillars, namely political, economic and social security, and sustainable development and relations between people. Meanwhile, 5 refers to five priority areas of cooperation, namely connectivity, production capacity, cross-regional economy, water resources, agriculture and poverty alleviation. Realizing the importance of water resources for economic growth encouraged Vietnam at the second summit in 2018 to show itself to be one step more active in this cooperation than several LMC member countries.   Keywords: Geopolitics; Lancang-Mekong Cooperation; Vietnam